Tailoring youth-friendly health services in Nigeria: a mixed-methods analysis of a designathon approach. Issue 1 (1st January 2021) - Nwaozuru, Ucheoma; Tahlil, Kadija M.; Obiezu-Umeh, Chisom; Gbaja-Biamila, Titilola; Asuquo, Sarah E.; Idigbe, Ifeoma; BeLue, Rhonda; Oladele, David; Muessig, Kathryn E.; Rosenberg, Nora E.; Ong, Jason J.; Musa, Adesola Z.; et al.
ABSTRACT: Background: Young people in low- and middle-income countries are often neglected in designing youth-friendly health services, especially HIV testing and preventive services. Designathons, which are time-bounded co-creation events where individuals gather in teams to develop solutions to a problem, could promote youth participation and ownership of health services. Objective: The purpose of this study is to examine youth participation in a designathon to create youth-friendly health services in Nigeria. Methods: Our designathon was based on crowdsourcing principles and informed by a human-centered design approach. The designathon included an open call for Nigerian youths between 14 and 24 years to share ideas on how to promote uptake of HIV self-testing services and a three-day sprint event that brought together diverse teams to develop strategies enhancing linkage to care. Teams pitched their solutions to a panel of five independent experts who scored ideas based on the desirability, feasibility, potential impact, and teamwork. We used descriptive statistics to summarize participants' demographics and conducted a content analysis to synthesize themes from youth proposals. Results: Nine hundred seventy-six youth across Nigeria applied to join the designathon. Forty-eight youth in 13 teams participated in the designathon with a median age of 20 years (IQR: 17–22]. Boys and young men were 48.5% (446/919) of the total applicants, 62.5% (30/48) of the designathon participants, and 63.6% (7/11) of the finalists. Students, from all educational levels, represented 91.2% (841/922) of the total applicants, 88.4% (38/43) of the designathon participants, and 90.0% (9/10) of the finalists. About twenty-three percent (3/13) of the final proposals were top ranked. The three finalist approaches to optimize youth-friendly health services centered on decentralizing service delivery to young people through mobile health technologies, use of mobile tents, or peer support services. Conclusions: Our open call engaged diverse groups of Nigerian youth, including young women and students. Our data suggest that designathons may be useful for developing tailored youth-friendly health services. Further research is needed to understand the designathon process and the effectiveness of the finalist submissions.